TRANSLATION OF ENGLISH LOCATIVE PREPOSITION PHRASES INTO INDONESIA (Content Analysis of Suharto : A Political Biography by R.E Elson and Its Translation) - Pebri Prandika Putra (Linguists : Journal Of Linguistics and Language Teaching, 2015)
The objective of this research is to understand comprehensively the translating of Englishlocative preposition phrase into Indonesia, It is a qualitative research with content analysismethod. The procedure of collecting data were first the writer read the original book and itstranslation detailed. Then, identified English locative preposition phrase and its translation.The data were analyzed according to research purpose. Findings of this study show thetranslation equivalances that used by translator are formal equivalance 58 data (44 %) anddynamic equivalence 72 data (55 %).